Real time noise-speech discrimination in time domain for speech recognition application - Mokhtar, Norrima; Arof, Hamzah; Adikan, Faisal Rafiq Mahamd; Mubin, Marizan (Academic Journals, 2011)
A simple noise-speech discrimination method in time domain is presented. The random signal noise characteristics were studied in time domain. Using the characteristics information, in real time processing, a simple algorithm to detect starting and ending point of speech samples in time domain is being demonstrated. Out of 100 attempts, about 94 of successful attempts of noise-speech discrimination have been obtained with white noise background by choosing the critical thresholds values.